Policy Reformulation of Legal Protection for Cooperating Offender Witnesses (Justice Collaborators): A Case Study of Richard Eliezer - Yoel, Veronika; Djatmika, Prija; Madjid, Abdul (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2025)
Proving a criminal act is the most crucial aspect of criminal law enforcement. Reflecting on the case of the premeditated murder of Brigadier Nofriansyah Yosua Hutabarat, which the main perpetrator and other perpetrators tried to cover up, one of the perpetrators, Richard Eliezer, took the courage to volunteer to become a Justice Collaborator. The problem arose when the legal protection given to a justice collaborator was not also given to his family. Based on this issue, this study aims to discuss the issue of legal protection for justice collaborators and their families with a case study of Richard Eliezer and to examine the reformulation of legal protection for justice collaborators and their families in Indonesia. This study uses a normative juridical method. The results of the study show that, reflecting on the reality of legal protection for Richard Eliezer as a justice collaborator in case No. 798/Pid.B/2022/PN JKT.SEL, normatively, legal protection for the families of justice collaborators has not been clearly regulated, because the LPSK is passive in protecting the families of justice collaborators. The conclusion of this study is that the reformulation policy on protection for witnesses who cooperate (justice collaborators) in Indonesia, primarily consists of specific technical rules regarding the protection of justice collaborators and their families